MSME FINANCIAL REPORT QUALITY SEEN FROM HUMAN RESOURCE COMPETENCE, IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS, AND SOCIAL CAPITAL - Lusy Lusy (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The quality of financial reports is very much needed by the entity as a business component and is useful in making decisions. The research was conducted to examine the quality of financial reports in terms of the competence of human resource, the application of Financial Accounting Standards (SAK), and social capital as a mediating variable. This study uses a quantitative approach using Partial Least Square (PLS). The population of this research is MSMEs on the slopes of Mount Arjuna. The sampling technique used was purposive sampling. The results of this study indicate that the competence of human resources and the application of SAK have an effect on the quality of financial reports. Meanwhile, social capital mediates both the competence of human resources and the application of SAK to the quality of financial reports. Social capital facilitates knowledge sharing, value creation, and competitive advantage, as well as better and faster performance and sustainable organizational development. The finding of social capital mediating human resource competence and the application of SAK is the novelty of this research